Association between body roundness index and serum 25-hydroxyvitamin D in women with and without breast cancer - Yajuan Du; Meixiang Huang; Tingting Su; Xiaoyan Huang; Zhenbin Zheng (Medicine, 2026)
Breast cancer (BC) is the most prevalent tumor in women, ranking first in incidence and mortality in many countries. Previous studies have suggested that. Body Roundness Index (BRI) is positively correlated with BC risk and negatively correlated with serum vitamin D levels. But few well-designed studies have explored the full impact of BC status on the relationship between BRI and serum vitamin D. So we aimed to evaluate the relationship between BRI and serum 25-hydroxy vitamin D in women without or with BC. We used data from the National Health and Nutrition Examination Survey to explore the association between BRI and serum 25-hydroxy vitamin D in women without or with BC. By stratifying participants according to BC status, we further assessed the difference between BRI and serum 25-hydroxy vitamin D levels in participants with and without BC using multivariate Linear regression (interaction test). A total of 21,774 participants were enrolled, comprising 21,212 non-BC patients and 562 BC patients. After adjusting for covariates, the association of BRI with serum 25-hydroxy vitamin D appeared to differ between non-BC group and BC group (β: −1.82, 95% confidence interval: −1.98~-1.66 vs β:-0.48,95%Cl: −1.67~0.71). Furthermore, when BRI was converted to a categorical variable, there was evidence of interaction between BC status and BRI in decreasing the levels of serum 25-hydroxy vitamin D ( P -value for interaction = .030). In non-BC patients, A nonlinear relationship was found between BRI and serum 25-hydroxy vitamin D, which had a threshold around 7.38; in BC patients, the relationship between BRI and serum vitamin D was not significant ( P = .434). Sensitivity analyses using propensity score matching yielded directionally consistent results, although the categorical interaction was no longer statistically significant. Our findings suggest a differential cross-sectional association between BRI and serum 25-hydroxyvitamin D in women with and without BC, which warrants confirmation in prospective studies.